Homework-Based Learning in the Teaching of Adjective Clause at English Education Program - Fatmawati, Rini (Universitas Muhammadiyah Surakarta, 2015)
Despite the various methods in delivering the subject of adjective clause, preference of the method and approach must be relevant to the objective the study. The objectives range from attitude, knowledge, and skill. In the learning process of adjective clause, the objective typesare affective and cognitive. Deductive approach is the most appropriate approach and homework-based learning is assumed to be relevant with the approach. Approach may be enclosed in the syllabus and the teachers have preferences to apply the most suitable approach. The approaches of teaching language emphasize on the theory of learning, how to learn and how to teach it. Applying the approach, an adjective clause theory starts with the presentation of the rule and it is followed by the practice. The procedure of teaching is based on the homework. This homework-based learning method applies several techniques of teaching simultaneously.